Penerapan Model Pembelajaran Group Investigation Dalam Meningkatkan Hasil Belajar Matematika - Halawa, Meiwati (JURNAL GLOBAL EDUKASI, 2020)
Abstract: This study aims to find out whether the application of the group investigation learning model can improve learning outcomes on the subject matter of building space for class IX-F students of SMP Negeri 1 Gunungsitoli. The results showed that the pre-cycle, the average learning outcomes and learning completeness in the pre-cycle were 52.97 and 26.32%. After the first cycle, the average learning outcomes and learning completeness increased to 57.89 and 52.63%. In the second cycle, after a reflection on the implementation of the action in the second cycle, the average learning outcome and learning completeness were 74.90 and 91.89%. From these results it is concluded that the application of the Group Investigation (GI) learning model on the subject matter of building space can improve the learning outcomes of students in Class IX-F SMP Negeri 1 Gunungsitoli for the academic year 2019/2020.Â Keywords: group investigation; geometryÂ Â Abstrak: Penelitian ini bertujuan untuk mengetahui apakah penerapan model pembelajaran Â group Â investigation Â dapat Â meningkatkan Â hasil Â belajar Â padaÂ  materi pokok bangun ruang bagi peserta didikÂ  Kelas IX-F SMP Negeri 1 GunungsitoliÂ  .â€ Hasil penelitian menunjukkan bahwa pra siklus diperoleh rata-rata hasil belajar dan ketuntasan belajar pada pra siklus adalah 52,97 dan 26,32%. Setelah dilakukan siklus I rata-rata hasil belajar dan ketuntasan belajar mengalami peningkatan yaitu menjadi 57,89 dan 52,63%. Pada siklus II setelah diadakan refleksi pelaksanaan tindakan pada siklus II mengalami peningkatan yaitu rata-rata hasil belajar dan ketuntasan belajar adalah 74,90 dan 91,89%. Dari hasil tersebut disimpulkan dengan penerapan model pembelajaran Group Investigation (GI) pada materi pokok bangun ruang dapat meningkatkan hasil belajar peserta didik Kelas IX-F SMP Negeri 1 Gunungsitoli Tahun Pelajaran 2019/2020.Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Kata Kunci: group investigation; bangun ruang